Environmental assessment of metal-organic framework DUT-4 synthesis and its application for siloxane removal - Piquinto-Garcia, Sandra; Rosas-Martínez, Juana María; Loredo-Cancino, Margarita; Giraudet, Sylvain; Soto-Regalado, Eduardo; Rivas-García, Pasiano; Dávila-Guzmán, Nancy Elizabeth (Elsevier, 2021)
In this study, the effect of different solvents in metal-organic framework (MOF) synthesis was evaluated in a technical study and an environmental study. The technical study considered the octamethylcyclotetrasiloxane (D4) adsorption on MOF DUT-4 for biogas purification, while the environmental study was implemented using the Life Cycle Assessment (LCA) methodology. In addition, the obtained DUT-4 adsorbents were characterized by X-ray diffraction, N2 adsorption-desorption isotherms, solid-state 27Al magic-angle spinning nuclear magnetic resonance, scanning electron microscopy, and Fourier transform infrared spectroscopy techniques. The results indicated that technically similar materials are obtained through solvothermal synthesis with similar D4 siloxane adsorption capacities (9.8 mg/g). Conversely, hydrothermal synthesis led to a low D4 siloxane adsorption capacity (1.8 mg/g). The environmental study demonstrated that the solvothermal synthesis had the highest contribution to the environmental damage due to the use of toxic solvents in the synthesis, cleaning, and solvent exchange stages (environmental score factor up to 244 mPt). In addition, a techno-environmental impact factor was introduced to identify the most suitable synthesis route of DUT-4. The overall results pointed out that solvothermal synthesis is the best scenario for DUT-4 production due to its low environmental impact/adsorption capacity ratio (11.44). This study is a step toward a more holistic approach integrating technical and environmental criteria in MOF synthesis for adsorption applications
Keywords: Siliconas; adsorption; LCA; MOF; Biogas